Revitalization Of Islamic Philanthropy In Empowering The Economy Of The People In The Digital Era - Chamid, Abdul; Olasunkanmi, Emiola Habeeb (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2025)
This study analyzes the revitalization of Islamic philanthropy in the economic empowerment of the ummah in the digital era by highlighting the potential and challenges of digitizing zakat, infaq, alms, and waqf (ZISWAF). Digitalization enables transparency and efficiency in the distribution of funds, expands community participation, and increases access to Islamic philanthropic services. However, challenges such as regulations that have not been fully supported, low digital literacy, and lack of innovation in distribution models remain obstacles. This study uses the content analysis method to identify patterns and trends in the management of digital Islamic philanthropy and Critical Discourse Analysis (CDA) to evaluate policy and regulatory narratives related to the digitization of zakat and waqf. The results of the study show that the digitization of Islamic philanthropy has great potential in improving social welfare and economic empowerment of the people, but requires a more systematic strategy and clear regulations. Strengthening governance based on sharia maqāṣid, digital education, and optimization of technology such as blockchain are the key to the sustainability of Islamic philanthropy in the digital era.